Students’ Writing Difficulties in Procedure Text: An Analysis Study - Heti Hidayah (Universitas Maritim Raja Ali Haji, 2021)
Abstract The function of writing skills is the most effective way to show someone’s English proficiency, including the ability and difficulties. The objective of this research was to know the factors and to the dominant factor of students’ writing difficulties in procedure text. The instruments of this research were interview and writing test as the support data. Therefore, the researcher conducted a descriptive qualitative study analysis. The technique in analysed the data of the interview was a descriptive analysis technique (percentage) and descriptive analysis technique without percentage to analyse the writing test. The researcher asked some aspects of students’ writing difficulties in writing procedure text based on the syllabus of class 9 K13 namely social function, structure text, language features, and topic. For the writing test, the students were asked to write a procedure text. So that the students had difficulties in social function, structure text, language features, and topic. This research showed the dominant factor students’ writing difficulties in procedure text was language features, like vocabulary and grammar which made the students difficult when writing the procedure text. Thus, the students still faced difficulties in writing skills like procedure text and the students have to improve their ability in writing skills. Keywords: Difficulty, Writing, Procedure Text